Renewable microgrid operational results and economic evaluation using RETScreenTM - Edison Banguero; Hector David Agudelo Arias; Andres Julian Aristizabal; Daniel Hernán Ospina Baragán (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This article describes the performance results of the first renewable microgrid of Chocó, Colombia, monitored over two years (2016-2017) adding an economic approach. A virtual platform is used to analyze, in real time, the microgrid power production, while a meteorological station measures the solar irradiance and the ambient temperature. The results indicated that the generation of AC PV energy was 21,817 kWh/year on 2016 and 23,301 kWh/year on 2017. The photovoltaic system’s average efficiency was 10.3 % on 2016 and 11.09 % on 2017. An economical analysis of the renewable microgrid is also presented using RETScreenTM software. The results show a net present value of $237,028 USD for an evaluation period of 25 years with annual energy savings of $4,622 USD. A calculation on greenhouse gas emissions show that 22.9 tCO2 per year are avoided  when using the solar energy tech.